1994
DOI: 10.1016/0735-1097(94)90289-5
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility for and benefit of thrombolytic therapy in inferior myocardial infarction: Focus on the prognostic importance of right ventricular infarction

Abstract: During acute inferior myocardial infarction, the right precordial electrocardiogram is a simple but promising variable to identify a subgroup of patients with an unfavorable course who will benefit most from thrombolytic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 39 publications
1
42
1
Order By: Relevance
“…23,24 Zehender and coworkers suggested that thrombolytic therapy reduced the in-hospital mortality and complication rate for patients with an inferior ventricular infarction with involvement of the right ventricle. 25 We also reported a similar finding in patients treated with thrombolysis during the acute phase of RVI. 7 Bowers and colleagues, in a PTCA-controlled study, suggested that complete reperfusion improves right ventricular function and the clinical outcome in patients with RVI.…”
Section: Discussionsupporting
confidence: 71%
“…23,24 Zehender and coworkers suggested that thrombolytic therapy reduced the in-hospital mortality and complication rate for patients with an inferior ventricular infarction with involvement of the right ventricle. 25 We also reported a similar finding in patients treated with thrombolysis during the acute phase of RVI. 7 Bowers and colleagues, in a PTCA-controlled study, suggested that complete reperfusion improves right ventricular function and the clinical outcome in patients with RVI.…”
Section: Discussionsupporting
confidence: 71%
“…Several of these observations [4,5] have quantified the degree of risk RVI contributes to the overall risk of death in patients with acute MI, but no work has established any prognostic measure within RVI patients alone. The development of the TIMI risk score [8] has created a useful tool with which to risk-stratify patients with acute MI.…”
Section: Discussionmentioning
confidence: 99%
“…While previous work has established the prognostic role of RVI in patients with inferior MI [3][4][5] , no work to date has attempted to stratify risk among patients with RVI.…”
Section: Introductionmentioning
confidence: 99%
“…Successful thrombolysis improves survival in patients with RVI, while the absence of reperfusion is associated with persistent dysfunction of the right ventricle and increased mortality [8][9][10][11]. Unsuccessful recanalization of the infarcted artery during fibrinolytic therapy occurs primarily in patients with proximal occlusion of the right coronary artery.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of these patients involves primarily early reperfusion. Reperfusion, either by thrombolysis or percutaneous coronary intervention (PCI) enhances the recovery of RV function and improves clinical outcome and survival [8][9][10].…”
Section: Introductionmentioning
confidence: 99%